1904 Md. Laws 295, An Act to Prohibit all Persons Under Fifteen Years of Age from Carrying or Having in Their Possession Firearms of any Description Within the Limits of Garrett County, ch. 177, §§ 1-2 - (:unkn) unknown (General Publisher, 1904)
§ 1. Be it enacted by the General Assembly of Maryland, That it shall be unlawful for all persons under the age of fifteen years to carry or have in his or her possession any shot gun, rifle, revolver or other firearm of any description within the limits of Garrett County. § 2. And be it enacted, That any person convicted of violating this Act before any court of competent jurisdiction shall be fined not less than five dollars nor more than twenty dollars, or be imprisoned in the county jail for not less than ten nor more than thirty days for each and every offense.
--
Keywords: POSSESSION - MINORS